POESÍA: EL ARTE FILOSÓFICO DE LA VERDAD (De la Crítica, 2023)
This article aims to show the philosophical ideal of poetry, taking into account the postulates of some thinkers of classical Greece (philosophical schools, the humanists and the wise Homer), the Middle Ages, even some of the most outstanding philosophers on modern and contemporary art, presenting the verses (words) as a truth artistic of what is communicated. Each one of them presents its own ideological proposals seeking to analyze the interior of the poet, his contributions and what his repercussions generate before the contemplative or spectator society. The Catholic Church itself through its documents expresses the fundamentals of poetry to catechize and to highlight the symbology in worship. Poetry is a literary art that through its verbal structure can create images, joy, pain and sadness.